Decreasing Blood Sugar Levels Through Modification of Diabetes Exercise and Peer Group Support (Indian Journal of Public Health Research & Development, 2020)
Background: The efforts to handle patients with type 2 diabetes mellitus need to consider both the physicaland psychological aspects. A physical activity that can be done is diabetes exercise. To do this exerciseregularly.Purpose: This study aims to analyze the effect of modified diabetes exercise and peer group support indecreasing blood sugar levels in patients with type 2 diabetes mellitus.Method: This study used a quasi-experimental design with a pre-test and post-test with 38 respondents,which consisted of 19 respondents for the intervention group and 19 respondents for the control group.They were selected by purposive sampling. Data was collected using aglucometer, observation sheets witha Standard Operating Procedure (SOP).Results: The results of the paired t test showed decreasing blood sugar levels after modified diabetes exerciseand peer group support in the intervention group with p value as much as 0.001 0.05.Conclusion: To control blood sugar levels through modified diabetes exercise and peer group support.
Keywords: Diabetes Mellitus, Diabetes Exercise, Peer Group Support, Blood Sugar Levels.